2020
DOI: 10.1021/acsomega.0c01825
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Mono-Triazole Derivative Modulate Aβ42 Aggregation and Disrupt a Protofibril Structure: Insights from Molecular Dynamics Simulations

Abstract: Clinical studies have identified that abnormal selfassembly of amyloid-β (Aβ) peptide into toxic fibrillar aggregates is associated with the pathology of Alzheimer's disease (AD). The most acceptable therapeutic approach to stop the progression of AD is to inhibit the formation of β-sheet-rich structures. Recently, we designed and evaluated a series of novel mono-triazole derivatives 4(a−x), where compound 4v was identified as the most potent inhibitor of Aβ 42 aggregation and disaggregates preformed Aβ 42 fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 117 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…However, in our opinion CHC will remain as the most probable target of BSBs and within it both phenylalanines 19 and 20 are supposedly crucial for the action of inhibitor molecules. This notion is also substantiated by the results obtained by use of different fibril models and small non‐peptide molecule inhibitors 52‐56 …”
Section: Discussionmentioning
confidence: 62%
“…However, in our opinion CHC will remain as the most probable target of BSBs and within it both phenylalanines 19 and 20 are supposedly crucial for the action of inhibitor molecules. This notion is also substantiated by the results obtained by use of different fibril models and small non‐peptide molecule inhibitors 52‐56 …”
Section: Discussionmentioning
confidence: 62%
“…The major factors that were considered by most of the researchers for evaluating the destabilization potential of the ligands are secondary structure content especially beta and coil content, salt bridge distance between Asp23-Lys28 (especially in U-shaped model), inter-chain hydrogen and hydrophobic interaction. 64,65,[81][82][83][84][85][86][87] In the current work, it was observed that binding of peptides with Abeta protobril has resulted in the loss of beta structure and gain of coil structure. This is in accordance with previous studies showing increase of coil and decrease of beta structures.…”
Section: Discussionmentioning
confidence: 86%
“…The U-shaped model (2BEG) has been part of most of the previously reported molecular simulation studies. [64][65][66][67][68][69][70] Thus, 2BEG model was selected for the study.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…1 Ab peptides are prone to misfolding, producing b-folded structures that ultimately lead to the self-association of peptides to form toxic substances. 2 The two most abundant Ab isoforms are Ab1-42 (Ab42 for short) and Ab1-40 (Ab40 for short), both of which are proteolytically cleaved by b-and g-secretases from the amyloid precursor protein (APP), a transmembrane precursor protein. 3,4 Ab42 has higher neurotoxicity and aggregation capacity than Ab40.…”
Section: Introductionmentioning
confidence: 99%